Atitude empreendedora e competência social: uma análise com empreendedores individuais e sociais - Barros, Izabel Cristina Ferraz (2012)
Entrepreneurship has been consolidated as one of the pillars to country development, through generation of incomes and work to population. However, entrepreneurship is not centered only on the business world. Nowadays a new branch of entrepreneurship is emerging, known as social entrepreneurship, whose main focus is social mission. Therefore, social competence must also be part of entrepreneurs' profile, both individual and social entrepreneurs, so that they are able to develop cooperative work relationships. This study is inserted in this context and it aimed to identify the relation between entrepreneur attitude and social competence according to the perception of individual and social entrepreneurs. Thus it was conducted a descriptive research with a quantitative approach. The population researched consisted of 136 managers who are members of Santa Maria Young Entrepreneurs Association and 36 managers of social organizations registered at the Social Organização Parceiros Voluntários , to whom a questionnaire was applied, which was developed with basis on the model proposed by Lopez Junior and Souza in 2005, named Measurement Instrument of Entrepreneur Attitude (IMAE). The second model consisted of questions related to social competence defined by Baron and Shane (2007). Statistic descriptive analyses were done such as distribution of frequencies, Correlation of Pearson and the Mann Whitney's Non-Parametric Test. The results led to family influence as the main reason for entrepreneur activity choice among individual entrepreneurs, and living with another entrepreneur as the second reason, while to social entrepreneurs the main reasons were necessity of helping needy people/communities and living with other entrepreneur. The analyses referring to Correlation of Pearson indicated positive correlations among all the dimensions of entrepreneur attitude, and social competence as well. Comparing the two groups studied through Mann-Whitney's Test, the results led to the existence of a significant difference between individual and social entrepreneurs regarding the social dimension. The other dimensions showed statistically no significant results to the two groups, and the social competence as well.